Physico-Chemical Analysis and Composition of Camel Milk of Bangladesh - Nilufar Nahar,; Waliul Islam Khan ,; Mohammad Shoeb, (Journal of Basic & Applied Sciences, 2016)
Camel farming is increasing in Bangladesh but the nutritious value of the produced milk has not been studied in this geological location. The milk was coagulated by citric acid and the coagulated solid i.e. the casein (7%) and pure serum (14%) were obtained. Fat content was determined by extracting casein and the aqueous serum, separately with n-hexane and found 2.59% and 5.79%, respectively. The fatty acids in the fat from casein and serum were made into their methyl ester by saponification followed by esterification and analyzed by GC-FID. Palmitoleic, oleic and linoleic acids were predominant fatty acids found in the analyzed samples while stearic, arachidic, behenic and myristic acids were present as minor acids. Water, ash, nitrogen and lactose contents in the milk were 84%, 0.88%, 1.62% and 9.32%, respectively. The presence of vitamin B1, B2 and B6 were estimated by UV-VIS spectrophotometer and found 388, 64 and 116 ppm, respectively.